Prognostic Significance of Glutathione Peroxidase Levels (GPx1) in Head and Neck Cancers - Dequanter, Didier; Dok, Ruveyda; Koolen, Louet; Vander Poorten, Vincent; Nuyts, Sandra (Frontiers in Oncology, 2017)
Introduction To date, no reliable prognostic biological marker for all squamous cell carcinoma located in different subsites of the head and neck region has been identified and used in daily routine. In line with our previous studies, in which we showed a role of glutathione and associated enzymes as potential biological markers, we investigated the relationship between GPx1 and prognosis of head and neck squamous cell carcinoma (HNSCC). Methods The association between GPx1 and patient and tumor related factors were investigated in 87 pretreatment biopsies from head and neck cancer patients treated by (chemo)radiation. Moreover, the influence of GPx1 expression on outcome parameters was assessed. Results A significant difference was found in the T-stage between the low and high expressing GPx1 groups. 75% of the T3-T4 tumors were considered GPx1 low expressing tumors, while low GPx1 expression was only seen in 25 % of the T1-T2 tumors. There was also a significant difference found between the groups when looking at the different tumor sites. No significant differences in local control, locoregional control, disease free survival and overall survival were found between the groups. All these results indicate that GPx1 expression does not influence the radiotherapy response nor survival.